Changes in dielectric properties of Pb(In1/2Nb1/2)O3-PbTiO3ceramics under compressive stress applied parallel and perpendicular to an electric field - M. Unruan (2018)
The influences of compressive stress on the dielectric properties of (1 - x)Pb(In1/2Nb1/2)O3-xPbTiO3(x = 0.1-0.5) ceramics was investigated in this study. The dielectric properties were measured under compressive stress applied parallel and perpendicular to electric field. The results clearly showed that the superimposed compression stress had pronounced effects on the dielectric properties of PIN-PT ceramics. In general, with increasing compressive stress the dielectric constant of the ceramics increased and decreased when the stress was applied parallel and perpendicular, respectively, to the electric field direction. The dielectric loss tangent, however, decreased in both stress cases. The observations were mainly interpreted in terms of competing influences of the domain switching through non-180° domain walls, clamping of domain walls, de-ageing and the stress-induced decrease in the switchable part of spontaneous polarization. © 2008 IOP Publishing Ltd.